(untitled) (Research, Society and Development, 2021)
The poor sanitation is one of the leading causes of disease worldwide. This factor, combined with the lack of proper health education, creates conditions conducive to disease transmission. The aim of this study was to describe the sanitation conditions related to Schistosomiasis in an Rural Settlements of Sergipe. The methodology was based on the collection of the local population data through a questionnaire.105 residents answered. 55.2% of them had tested positive, and 44.8% negative, 49% of the positive cases, reported that they did not take specific medication for the treatment of disease. Related to knowledge about MS, 76.2% reported having no knowledge, 21% little, and 2.9% good knowledge. 69% of the habitants infected had an intense degree of contact with water. Thus, it is concluded that the precariously occupation of the region, without the existence of the necessary sanitation conditions, and no knowledge about the disease provides favorable environments for disease transmission.